2015
DOI: 10.1099/mic.0.083410-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Agrobacterium tumefaciens virulence protein VirD2 with histones

Abstract: Agrobacterium tumefaciens is a Gram-negative soil bacterium that genetically transforms plants and, under laboratory conditions, also transforms non-plant organisms, such as fungi and yeasts. During the transformation process a piece of ssDNA (T-strand) is transferred into the host cells via a type IV secretion system. The VirD2 relaxase protein, which is covalently attached at the 59 end of the T-strand through Tyr29, mediates nuclear entry as it contains a nuclear localization sequence. How the T-strand reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It has been shown that the agrobacterium proteins VirE2, which coats the T‐DNA, and VirD2, which attaches to 5’ end of the T‐DNA and mediates nuclear entry, both associate with cellular histones (Lacroix et al ., ; Wolterink‐van Loo et al . ). As MAR are thought to influence chromatin structure, the association of T‐DNA with histones suggests a possible mechanism by which MAR function in vectors delivered by agroinfiltration.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the agrobacterium proteins VirE2, which coats the T‐DNA, and VirD2, which attaches to 5’ end of the T‐DNA and mediates nuclear entry, both associate with cellular histones (Lacroix et al ., ; Wolterink‐van Loo et al . ). As MAR are thought to influence chromatin structure, the association of T‐DNA with histones suggests a possible mechanism by which MAR function in vectors delivered by agroinfiltration.…”
Section: Discussionmentioning
confidence: 97%
“…VirD2 contains NLS that guide the T‐complex to the nucleus of the host cell (Ziemienowicz et al ., ). Ectopically expressed GFP−VirD2 has a nuclear localization in both yeast and plant cells (Citovsky et al ., ; Wolterink‐van Loo et al ., ). In this study we found a similar localization for both GFP 11 ‐ and phiLOV2.1‐tagged VirD2 ectopically expressed in yeast (Figures and S1).…”
Section: Discussionmentioning
confidence: 97%
“…The translocated VirD2 is most likely located in the nucleus, but because of the low amount of translocated VirD2 we were unable to determine the exact subcellular localization. Using the BiFC approach translocated VirD2 was shown to interact with yeast nuclear histone proteins (Wolterink-van Loo et al, 2015). phiLOV2.1ÀVirD2 translocated to A. thaliana root cells was found in the nucleus (Figure 4), whereas in N. tabacum leaves it was found in dot-shaped structures close to or at the cell membrane ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…One option to solve this problem could be a mechanism that targets the T-DNA to DSBs that are, for example, created by DNA topoisomerases during transcription or replication. It is interesting to note that VirD2 has been shown to interact with yeast histones (Wolterink-van Loo et al, 2015). One may speculate that histone phosphorylation upon DSB detection (Waterworth et al, 2011) might serve as a signal to guide VirD2 and the T-strand to DSBs.…”
Section: Plant Repair Pathway For T-dna Integrationmentioning
confidence: 99%